2021
DOI: 10.1111/dme.14750
|View full text |Cite
|
Sign up to set email alerts
|

Learning challenges of healthcare professionals supporting open‐source automated insulin delivery

Abstract: Background: Open-source automated insulin delivery (AID) is a user-driven treatment modality used by thousands globally. Healthcare professionals' (HCPs) ability to support users of this technology is limited by a lack of knowledge of these systems. Aims: To describe the challenges experienced by HCPs supporting participants' use of open-source automated insulin delivery in the Community deRivEd AuTomatEd insulin delivery (CREATE) study. Methods: Data were collected prospectively from the study team's fortnigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…However, interview data show participants reported improved psychosocial outcomes. The authors state that multiple factors may have impacted the PROM findings, including low numbers of participants and control arm participants having funded access to CGMs [44]. Comparatively, this study has shown significant differences between those using open-source AID and nonusers in QoL, diabetes treatment satisfaction, and fear of hypoglycemia, plus additional apparent benefits.…”
Section: Overviewmentioning
confidence: 80%
“…However, interview data show participants reported improved psychosocial outcomes. The authors state that multiple factors may have impacted the PROM findings, including low numbers of participants and control arm participants having funded access to CGMs [44]. Comparatively, this study has shown significant differences between those using open-source AID and nonusers in QoL, diabetes treatment satisfaction, and fear of hypoglycemia, plus additional apparent benefits.…”
Section: Overviewmentioning
confidence: 80%
“…In a survey of 104 school nurses, 23% reported a child using DIY AID attended their school, 46% stated they had no prior knowledge of DIY AID and 96% felt the child should be able to share their data with a parent or guardian during the school day [ 46 ]. HCP supporting AndroidAPS use as part of the Community Derived Automated Insulin Delivery study (CREATE) in New Zealand [ 81 , 82 ], found that user challenges with this system most frequently related to device issues (the insulin pump and cannula in 24% of analyzed conversations), as opposed to DIY AID specific challenges [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Overall, much of the troubleshooting will be about the components of the system rather than diabetes itself [ 43 ] because the AID system, when operational, can help address much of the “noise” of blood glucose variation associated with insulin-requiring diabetes [ 35 ]. This change in behavior from managing insulin delivery manually to managing the devices used to automate insulin delivery will require learning and habit formation.…”
Section: Troubleshooting Aid and Ensuring The Basic Operation Of Aidmentioning
confidence: 99%